Animasyon Sinemasına Ekoeleştirel Yaklaşım: “Wall-E” Filminin İncelenmesi - Güngör, Arif Can (The Turkish Online Journal of Design Art and Communication, 2015)
Our century is an age of science and technology. At the same time, degradation of ecological balance and environmental pollution problems are in a parallel course against scientific and technological development. This constantly produces to new paradigms in issues about technology and degradation of ecological balance. Human, disrupts ecological balance, puts into words the existing results and/or eventuality of this degradation with narratives and can also provides solutions. In this context, the animation film “Wall-E” was investigated in the article how put forward in the reasons and results of degraded ecological balance. In the research, approach of the film that criticizes environmental pollution in the world was tackled with an ecocritical paradigm. One of the most admired animation film in the recent Wall-E was observed from first day to present in the article. Environmental problems are introduced can be listed like this: what critics are mentioned, whether have a view to greenwashing or not are examined with the analysis of discourse from the topics or not; “Shallow Ecology of the Consumer Society”, “Adam and Eva”, “Axiom from Utopia to Dystopia”, “Conflict of Human-Machine and New Materialism”. Althouhg Wall-E criticized to capitalism and consumer society and was a product of it, seems problematic about making a deep ecological perspective.
Keywords: Ekoeleştiri; Canlandırma; Film; Çevre; Sinema; Ecocritic; Animation; Movie; Environmental; Cinema